Mechanical response of the flux lines in ceramic YBa2Cu3O7- - Luzuriaga, J.; Andre, M.-O.; Benoit, W. (American Physical Society, 1992)
Fil: Luzuriaga, J. Comisión Nacional de Energía Atómica. Instituto Balseiro; Argentina; Universidad Nacional de Cuyo; Argentina; Ecole Politechnique Federal de Lausanne; Suiza